Конструкторская разработка изделий в среде Creo Parametric: учебное пособие - Пушкарев М. И. Максим Иванович; Фадеев А. С. Александр Сергеевич; Суходоев М. С. Михаил Сергеевич; Ефимов С. В. Семён Викторович; Журман Д. А. Дмитрий Александрович (Томск, Изд-во ТПУ, 2018)
Заглавие с титульного экрана